Processing Mixture of Polypropylene (PP) Plastic Waste and Palm Fiber Waste into Alternative Fuels - Ibnatun Rif'ah; Rosyani Rosyani; Nazarudin Nazarudin (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2022)
AbstractThe increasing accumulation of plastic and industrial biomass wastes, as well as the declining reserves of petroleum as an energy source, have become significant topics of discussion. Therefore, this research aims to determine alternative energy sources in the form of fuel derived from cracking a mixture of Polypropylene (PP) plastic and palm fiber (SKS) waste. It also aims to determine the quantity and quality of the derived products. The cracking process with a catalyst to feed ratio of 1:10 and a time of 40 minutes led to the highest % conversion Cracking Result Liquid (CHP) product of 48.08% with the variation condition of PP to SKS ratio of 1.5:1 at a temperature of 500°C. The GC-MS analysis results showed that the % area of the CHP product contains fuels, such as gasoline (32.97%), kerosene (5.36%), and diesel (2.24%).Keywords: Cracking, Polypropylene, plastic waste, palm fiber, alternative energi Abstrak (Indonesian)Meningkatnya akumulasi limbah, baik itu sampah plastik maupun limbah biomassa hasil industri, serta menurunnya cadangan minyak bumi sebagai sumber enegi, menjadi topik masalah yang cukup signifikan untuk dibahas dan dicarikan solusinya. Penelitian dilakukan dengan tujuan mencari sumber energi alternatif berupa bahan bakar yang berasal dari perengkahan campuran sampah plastik jenis PP (Polypropylene) dan limbah biomassa serabut kelapa sawit (SKS), serta mengetahui kuantitas dan kualitas produk yang dihasilkan. Perengkahan yang dilakukan dengan perbandingan katalis dan umpan 1:10 dan waktu 40 menit, menghasilkan %konversi produk CHP (Cairan Hasil Perengkahan) tertinggi sebesar 48,08% dengan kondisi variasi rasio PP:SKS adalah 1,5:1 dan suhu 500°C. Hasil analisa GC-MS menunjukkan % area produk CHP tersebut mengandung bahan bakar seperti bensin (32,97%), minyak tanah (5,36%) dan solar (2,24%). Kata Kunci : Perengkahan, Polypropylene, sampah plastik, serabut kelapa sawit, energi alternatif